2021
DOI: 10.1038/s42255-021-00482-9
|View full text |Cite
|
Sign up to set email alerts
|

Slit3 secreted from M2-like macrophages increases sympathetic activity and thermogenesis in adipose tissue

Abstract: Beiging of white adipose tissue (WAT) is capable of adaptive thermogenesis and dissipating energy. The beiging processes have been associated with the increase of anti-inflammatory M2 macrophages, however the function of M2 macrophage on beiging and the underlying mechanism are not fully understood. Here we identified a macrophage cytokine Slit3 by analyzing the transcriptome of M2 macrophages collected with FACS in inguinal WAT (iWAT) of mice after cold exposure. Once released from macrophages, Slit3 bound to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 64 publications
1
47
0
Order By: Relevance
“…Instead, it was linked to sustaining sympathetic innervation and adaptive thermogenesis at a steady-state for homeostasis. As discussed, alternatively activated macrophages have also been reported to involve sympathetic nerve outgrowth in subcutaneous WAT during cold adaptation ( 16 , 60 ). Therefore, available evidence indicates that a discrete subpopulation of ATMs may reshape local sympathetic innervation to mediate energy expenditure and maintain metabolic homeostasis.…”
Section: The Adipose Macrophages Central To Adaptive Thermoregulationmentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, it was linked to sustaining sympathetic innervation and adaptive thermogenesis at a steady-state for homeostasis. As discussed, alternatively activated macrophages have also been reported to involve sympathetic nerve outgrowth in subcutaneous WAT during cold adaptation ( 16 , 60 ). Therefore, available evidence indicates that a discrete subpopulation of ATMs may reshape local sympathetic innervation to mediate energy expenditure and maintain metabolic homeostasis.…”
Section: The Adipose Macrophages Central To Adaptive Thermoregulationmentioning
confidence: 98%
“…A recent study provided a novel aspect of M2 macrophage-dependent catecholamine secretion and beiging by discovering the mechanism by which M2 macrophages enhanced the local SNS activation in subcutaneous WAT upon cold exposure. Slit guidance ligand 3 (SLIT3) secreted from M2 macrophages induced sympathetic innervation and TH activation by binding to sympathetic neurons via roundabout guidance receptor 1 (ROBO1), thereby promoting NE synthesis and beiging to sustain adaptive thermogenesis ( 16 ). Consistent with this notion, an independent study found that IL-25-induced M2 macrophage polarization increased outgrowth of sympathetic nerves in subcutaneous WAT ( 60 ).…”
Section: The Adipose Macrophages Central To Adaptive Thermoregulationmentioning
confidence: 99%
“…There is emerging evidence regarding the non-canonical functions of AT immune cells beyond immune-modulation, including angiogenesis and browning/beiging [ 105 , 113–115 ]. In addition to their anti-inflammatory properties, the M2-like ATMs are activated during a cold challenge to secrete the signalling protein SLIT3, which promotes the AT sympathetic nerve fibres to release norepinephrine and to nudge the white adipocytes into thermogenic adipocytes [ 116 ]. Similarly, tissue-resident γδ T cells, which are required for T regulatory cell accumulation, have crucial involvement in adaptive thermogenesis and brown AT innervation [ 58 , 117 ].…”
Section: Reprogramming By Immune Modulationmentioning
confidence: 99%
“…Slit3 is a macrophage cytokine secreted by ATM. It binds to the ROBO1 receptor to stimulate Ca2+/calmodulin-dependent protein kinase II signaling and NE release, which enhances adipocyte thermogenesis ( Wang et al, 2021 ). Additionally, MMs regulate peristaltic activity of the colon by secreting bone morphogenetic protein 2 (BMP2), which activates the expression of BMP receptor on enteric neurons.…”
Section: Tissue-specific Immune Effects On Nervesmentioning
confidence: 99%